کارى(بیەى = بوون) لە زارى هەورامیدا - عەبدول, فەرەیدون (Sulaimani Journal for Humanities, 2000)
This research deals with verb “ boon “ ( verb to be ) in AlHawramya dialect. This verb can be used in for different ways to give four different meanings. 1. verb to be. 2. verb to become. 3. verb to have . 4. verb to be ( existence ). In the first three cases the verb needs a complement to be used before or after it, but in the fourth case it does not need a complement . A personal pronominal suffix is used from one of the five groups in Al-Hawramya dialect as a paradigm of the form of the verb. The importance of this research is that it is a practical guide which illustrates the uses of this verb , which can be benificial to comparative linguistic studies and to comparison bewteen the kurdish dialects.